Models and Strategies for BIPA Teacher Training (2009–2024): A Systematic Review of Southeast Asia and the United States - Alim Harun Pamungkas; Rizki Putri Ramadhani; Rodolfo Soares; Bunga Febrimora Hendri; Fatah Nasikh Aryawan; Putra Ramadani; Anggi Firmanjaya Saputra (AL-ISHLAH: Jurnal Pendidikan, 2026)
Law No. 24/2009 positions Bahasa Indonesia as a prospective international language and promotes Bahasa Indonesia untuk Penutur Asing (BIPA) as a strategic instrument of cultural diplomacy. However, empirical evidence on effective training models for teachers and learners across international contexts remains fragmented. This study synthesizes research on BIPA training models and their pedagogical implementation in Southeast Asia and the United States from 2009 to 2024.A systematic literature review was conducted following the PRISMA 2020 protocol. Searches in Scopus, ERIC, and Google Scholar (March 2024) yielded 312 records. After screening and eligibility assessment based on predefined criteria, 15 studies were included. Study quality was appraised using the MMAT (2018), and findings were analyzed through weighted thematic synthesis.The evidence is dominated by Indonesia-based studies with international orientation (n=9), followed by Southeast Asia (n=3), the United States (n=2), and transnational contexts (n=1). Three major thematic clusters emerged: (1) curriculum standardization, particularly CEFR adaptation; (2) technology-oriented professional development; and (3) exchange and mentoring models. Distinct contextual logics were identified, with Southeast Asia emphasizing regional integration and institutional expansion, while the United States focuses on sustaining Less Commonly Taught Languages (LCTLs).Effective internationalization of BIPA requires networked teacher professional development integrating TPACK frameworks and mentoring, alongside shared curriculum repositories aligned with CEFR and local cultural contexts. However, the limited and predominantly descriptive evidence base—especially in the U.S. context—suggests that findings remain provisional. Further empirical and comparative research is needed to strengthen global BIPA training models and policy implementation.